Relief Effects of Icariin on Inflammation-Induced Decrease of Tight Junctions in Intestinal Epithelial Cells - Yanli Li; Jie Liu; Pawin Pongkorpsakol; Zhengguo Xiong; Zhengguo Xiong; Li Li; Li Li; Xuemei Jiang; Xuemei Jiang; Haixia Zhao; Ding Yuan; Changcheng Zhang; et al. (Frontiers in Pharmacology, 2022)
Inflammatory cytokines including TNF-α and IL-1β impair intestinal barrier function in aging by disrupting intestinal tight junction integrity. Icariin (ICA) has a variety of pharmacological effects. Indeed, ICA produces anti-inflammatory, anti-oxidative stress, and inhibitory effects on microRNA (miRNA) expression. This study was to explore whether ICA could alleviate inflammation-associated intestinal barrier function impairment in aging and its underlying mechanism. Of particular interest, network pharmacology prediction indicated the potential therapeutic impacts of ICA for the treatment of colitis. Then, rats were used to study whether ICA has a protective effect on the reduction of tight junctions caused by inflammatory cytokines. Next, Caco-2 cell monolayers were used to explore the mechanism by which ICA alleviates the down-regulation of tight junctions. Network pharmacology prediction revealed that ICA alleviated colitis via suppressing oxidative stress. After ICA intervention, expressions of inflammatory cytokines were reduced, but tight junctions, antioxidant enzymes in aging rats were up-regulated. ICA reversed the TNF-α-induced decrease in abundance of Occludin protein in Caco-2 cell monolayers. Meanwhile, ICA alleviated the increase in permeability and expression of miR-122a. However, the protective effect of ICA was markedly attenuated after transfection with miR-122a mimics. In conclusion, ICA reduced the expressions of Occludin, Claudin1, and Claudin5 in colon, which were related to the reduction of TNF-α and IL-1β and alleviation of colonic in vivore. And ICA attenuated TNF-α-induced Occludin disruption and epithelial barrier impairment by decreasing miR-122a expression in Caco-2 cell monolayers.